2007
DOI: 10.1158/0008-5472.can-06-3699
|View full text |Cite
|
Sign up to set email alerts
|

A Transgenic Mouse Model of Plasma Cell Malignancy Shows Phenotypic, Cytogenetic, and Gene Expression Heterogeneity Similar to Human Multiple Myeloma

Abstract: Multiple myeloma is an incurable plasma cell malignancy for which existing animal models are limited. We have previously shown that the targeted expression of the transgenes c-Myc and Bcl-X L in murine plasma cells produces malignancy that displays features of human myeloma, such as localization of tumor cells to the bone marrow and lytic bone lesions. We have isolated and characterized in vitro cultures and adoptive transfers of tumors from Bcl-xl/Myc transgenic mice. Tumors have a plasmablastic morphology an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 59 publications
0
40
0
Order By: Relevance
“…42,43 The Em-Bcl-2 transgene has also been shown to accelerate plasmacytoma development in Vk*MYC mice, 13 as did coexpression of bcl-x L and myc transgenes late in B-lymphoid ontogeny. 25,26,44 Remarkably, despite the increase in peripheral T-and B-lymphoid cells provoked by inhibition of apoptosis (supplemental Figure 2) and expression of the v-abl transgene in these compartments (Figure 1; supplemental Figure 1), with one exception (see above), no lymphomas arose in bim 2/2 v-abl, mcl-1/v-abl, or bcl-2/v-abl mice. It therefore seems likely that plasma cells are the primary targets for transformation in Em-v-abl mice (see below).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…42,43 The Em-Bcl-2 transgene has also been shown to accelerate plasmacytoma development in Vk*MYC mice, 13 as did coexpression of bcl-x L and myc transgenes late in B-lymphoid ontogeny. 25,26,44 Remarkably, despite the increase in peripheral T-and B-lymphoid cells provoked by inhibition of apoptosis (supplemental Figure 2) and expression of the v-abl transgene in these compartments (Figure 1; supplemental Figure 1), with one exception (see above), no lymphomas arose in bim 2/2 v-abl, mcl-1/v-abl, or bcl-2/v-abl mice. It therefore seems likely that plasma cells are the primary targets for transformation in Em-v-abl mice (see below).…”
Section: Discussionmentioning
confidence: 93%
“…67 Plasmacytomas arising in bcl-x L /myc bi-transgenic mice also have significantly increased expression of cyclin D1 RNA but lower levels of cyclin D2 RNA. 44 Ectopic expression of CCND1 is frequent in human mantle cell lymphoma, and transgenic studies have shown that Myc and cyclin D1 synergize in B lymphomagenesis in mice. 68,69 It is instructive to compare the molecular features described here for v-abl mouse plasmacytomas with those of human MM, which is notable for its genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Double-transgenic Bcl-X L /Myc mice develop plasma cell tumors (mean onset of 135 days) with full (100%) penetrance that possess many of the karyotypic, phenotypic, and gene expression features of human multiple myeloma (13, 14). Furthermore, malignant plasma cells can be isolated from these animals, expanded, modified in vitro , and subsequently transferred back into syngeneic mice for drug treatment in the presence of an active immune system, which includes a complete bone marrow microenvironment (13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…3 We have employed this model system because malignant plasma cell lines isolated from these mice closely resemble human MM based on gene expression, chromosomal abnormalities and progression of disease in the bone marrow. 35 Perhaps most importantly, from initially drug-sensitive tumor cell populations we are able to select for drug-resistant cells in vitro , adoptively transfer these cells back into syngeneic recipient mice, and recapitulate the drug-sensitive or -resistant phenotype following in vivo Bz treatment of recipient mice. 3 Remarkably, the differences in Bz sensitivity in our mouse cell lines strongly correlated with differences in malignant plasma cell migration following adoptive transfer.…”
mentioning
confidence: 99%